Dynamic Changes of Microglia/Macrophage M1 and M2 Polarization in Theiler's Murine Encephalomyelitis - Herder, Vanessa (Brain Pathol, 2015)
Microglia and macrophages play a central role for demyelination in Theiler's murine encephalomyelitis (TME) virus infection, a commonly used infectious model for chronic‐progressive multiple sclerosis. In order to determine the dynamic changes of microglia/macrophage polarization in TME, the spinal cord of Swiss Jim Lambert (SJL) mice was investigated by gene expression profiling and immunofluorescence. Virus persistence and demyelinating leukomyelitis were confirmed by immunohistochemistry and histology. Electron microscopy revealed continuous myelin loss together with abortive myelin repair during the late chronic infection phase indicative of incomplete remyelination. A total of 59 genes out of 151 M1‐ and M2‐related genes were differentially expressed in TME virus‐infected mice over the study period. The onset of virus‐induced demyelination was associated with a dominating M1 polarization, while mounting M2 polarization of macrophages/microglia together with sustained prominent M1‐related gene expression was present during the chronic‐progressive phase. Molecular results were confirmed by immunofluorescence, showing an increased spinal cord accumulation of CD16/32(+) M1‐, arginase‐1(+) M2‐ and Ym1(+) M2‐type cells associated with progressive demyelination. The present study provides a comprehensive database of M1‐/M2‐related gene expression involved in the initiation and progression of demyelination supporting the hypothesis that perpetuating interaction between virus and macrophages/microglia induces a vicious circle with persistent inflammation and impaired myelin repair in TME.